Modul STEM Berbasis Pemecahan Masalah dengan Tema Rumah dome - Ziyyan Alieffia Alfika; Tantri Mayasari; Erawan Kurniadi (UNIVERSITAS MUHAMMADIYAH METRO, 2019)
This study aims to describe in detail the results of the development of a problem-solving STEM module with the theme of the dome house, and explain the results of the improvement after the use of the module. STEM is an approach that combines science, technology, engineering, and mathematics into a single discipline that is able to realize learning by presenting real problems in everyday life. The STEM module based on the problem-solving ability developed raised the theme of the dome house, which has a function as an earthquake-resistant house which was used as a reconstruction of post-earthquake housing and is permanent, economical, and efficient. Solving problems is one part of high-level thinking, as well as a form of action in solving problems that utilize the knowledge they have. Indicator of achievement of problem solving is analyzing the problem, making a plan for its completion, carrying out planning, and checking again. The development method applied is Research and Development. This module is validated by 5 experts, the results show that the module is very feasible to use. The module was tested on research subjects totaling 20 eighth grade students. The results show that the highest increase in students' problem-solving ability after the implementation of the module is the indicator carrying out the plan with n-gain 0.40, while the lowest increase in the indicator understands the problem with n-gain 0.22. Overall, the STEM module that was developed was able to improve the problem solving ability of state Islamic junior high school students.